2022
DOI: 10.1007/s00299-022-02958-8
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of knockout mutants of rice seed dormancy gene OsVP1 and Sdr4

Abstract: Seed dormancy and germination are critical agricultural traits influencing rice grain yield. Although there are some genes have previously identified, the comprehensive understanding on large-scale transcriptome is deficient. In this study, we generated mutants of two representative regulators of seed germination, Oryza sativa Viviparous1 (OsVP1) and Seed dormancy 4 (Sdr4), by CRISPR/Cas9 approach and named them cr-osvp1 and cr-sdr4. The weakened dormancy of mutants indicated that the functions of OsVP1 and Sd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…The pyrabactin resistance 1 ( PYR1 )/ PYR1‐like / regulatory components of ABA receptors ( PYR/PYL/RCAR ) family members of wheat TaPYL4 have been reported to promote seed dormancy when overexpressed (Mega et al, 2019). Viviparous‐1 ( Vp1 ) (homologous to ABSCISIC ACID INSENSITIVE3 of Arabidopsis thaliana , ABI3 ) plays a major regulatory role in seed dormancy, with mutants of vp1/abi3 in maize, rice, and Arabidopsis displaying weak dormancy and are prone to PHS (McCarty et al, 1991; Nambara et al, 1995; Chen et al, 2020). Previous studies have demonstrated a positive correlation between the expression level of TaVP1 and wheat dormancy (Yang et al, 2007; Chang et al, 2009; Feng et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The pyrabactin resistance 1 ( PYR1 )/ PYR1‐like / regulatory components of ABA receptors ( PYR/PYL/RCAR ) family members of wheat TaPYL4 have been reported to promote seed dormancy when overexpressed (Mega et al, 2019). Viviparous‐1 ( Vp1 ) (homologous to ABSCISIC ACID INSENSITIVE3 of Arabidopsis thaliana , ABI3 ) plays a major regulatory role in seed dormancy, with mutants of vp1/abi3 in maize, rice, and Arabidopsis displaying weak dormancy and are prone to PHS (McCarty et al, 1991; Nambara et al, 1995; Chen et al, 2020). Previous studies have demonstrated a positive correlation between the expression level of TaVP1 and wheat dormancy (Yang et al, 2007; Chang et al, 2009; Feng et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…With the development of omics technology, such as transcriptomics and metabolomics, these have been widely used to fully understand the effects of gene knockout on the body [27][28][29]. Transcriptomic profiling is a powerful tool that identifies gene expression signatures [30].…”
Section: Introductionmentioning
confidence: 99%
“…The precise genome editing enabled by CRISPR/Cas9 has the potential to greatly enhance the quality and yield of agricultural production, while also facilitating the creation of new and improved varieties of rice with enhanced traits [ 28 , 29 , 30 , 31 , 32 ]. In recent years, the beneficial integration of CRISPR/Cas9 and high-throughput transcriptome sequencing technology (RNA-seq) has opened up new possibilities for investigating gene function [ 33 , 34 ]. Simultaneously, with the development of molecular biology technology, RNA-seq has been widely used in the study of gene expression levels and regulatory networks [ 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%